PENGUKURAN KINERJA UNIT KERJA PEMERINTAH DAERAH DALAM PERSPEKTIF VALUE FOR MONEY (Studi Pada Dinas Koperasi dan UMKM Kota Surabaya) - Nada, Syaza Lifia; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to measure, to analyze and to find out the performance at Cooperation Department and Micro, Small, and Medium enterprises in Surabaya city which is measured by using value for money concept. The research method has been carried out by using qualitative. The data collection technique has been conducted by using interview and documentation. Meanwhile, the analysis of performance appraisal has been done on the basis of economic, efficient, effectiveness performance which refers to input, output, and outcome. The result of the discussion and the analysis about performance appraisal at work unit of Local Government in the perspective of value for money in the Cooperation Department and Micro, Small, and Medium enterprises in Surabaya city in 2014-2015 periods shows that in determining economic performance it is done by considering the budget (input) and budget realization. The efficient performance is considered from the amount of the realization f output which has been generated to the input. The effective performance is considered from the output or the outcome which has been succeeded in running the objective of the institution in achieving the expected program. Even though the performance report of Cooperation Department and Micro, Small, and Medium enterprises in Surabaya city shows the achievement of the performance of economic, efficient, and effectiveness is in accordance with the expectation. Nevertheless, the improvement of relevant performance appraisal model is required, by considering the relevancy of the purpose of the activity and the program.Keywords : Value for money, economic, efficient, effectiveness